Bahasa dan Pandangan Hidup Masyarakat Jawa Terkait Aktivitas Pertanian Padi di Desa Tladan Kecamatan Kawedanan Kabupaten Magetan (Kajian Etnolinguistik) - Anjarwati, Nanda (Sutasoma : Jurnal Sastra Jawa, 2020)
Ethnolinguistics is a study that connects linguistic concepts related to culture in local communities. The people in Tladan village, Kawedanan district, Magetan regency are still familiar with the terms rice farming activities from generation to generation, so the relationship between Javanese language and culture in the use of the term rice farming activities can be studied with an etnolinguistik approach.The purpose of this research is (1) to describe the form of language in Javanese culture related to rice farming activities in Tladan Village, Kawedanan district,Magetan regency (2) to describe the lexical, gramatical and cultural meanings summarized in Javanese languages and culture related to rice farming activities in Tladan Village, Kawedanan district,Magetan regency (3) describes the mindset, perspective on life, and the world of the peasant community in Tladan Village in Tladan village, Kawedanan district, Magetan regency. This type of research is basic research, the level of this research is descriptive qualitative.The data was collected using farming activity observation techniques, proficient methods, and literature study. The data research were analyzed by distribution method (distributional) and the equivalent method. This result of this study are (1) the form of language described by monomorphemic, polymorphemic, and phrases contained in the language in Javanes culture related to rice farming activities in Tladan Village, Kawedanan district,Magetan regency (2) the lexical,gramatical, and cultural meanings contained in the language of Javanese culture related to rice farming activities in Tladan Village, kawedanan district, Magetan regency (3)mindset, perspective of life, and the world of the peasant community in Tladan Village, Kawedanan district, Magetan regency. Keywords : ethnolinguistics, rice farming, Magetan, Tladan